Konsep Syirkah pada Perbankan Syariah - Hanafi Hadi Susanto (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2016)
The concept of syirkah (partnership) in Islamic banking is the main foundation in implementing the principles of justice and profit-sharing in accordance with Islamic law. Through mudharabah, musyarakah, or wakalah schemes, Islamic banks not only avoid usury but also encourage productive collaboration between banks and customers, both in business financing and investment. The implementation of syirkah not only strengthens financial inclusion based on Islamic values, but also creates a more stable and equitable economic ecosystem. This research examines the practices, challenges and impacts of syirkah in Islamic banking, as well as its relevance in supporting sustainable economic development.